2011
DOI: 10.1158/1940-6207.capr-11-0095
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of PDE5 by Sulindac Sulfide Selectively Induces Apoptosis and Attenuates Oncogenic Wnt/β-Catenin–Mediated Transcription in Human Breast Tumor Cells

Abstract: Nonsteroidal anti-inflammatory drugs (NSAIDs) such as sulindac sulfide (SS) display promising antineoplastic properties, but toxicities resulting from cyclooxygenase (COX) inhibition limit their clinical use. While COX inhibition is responsible for the anti-inflammatory activity of SS, recent studies suggest that phosphodiesterase (PDE) 5 inhibition and activation of cGMP signaling are closely associated with its ability to induce apoptosis of tumor cells. However, the underlying mechanisms responsible for apo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
112
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(116 citation statements)
references
References 26 publications
3
112
0
1
Order By: Relevance
“…Because inflammation is closely associated with tumorigenesis, COX-2 has been shown to be overexpressed in precancerous and malignant lesions [33,34,35]. Its inhibition and the suppression of prostaglandin synthesis is widely accepted as the primary mechanism of the anticancer activity of NSAIDs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because inflammation is closely associated with tumorigenesis, COX-2 has been shown to be overexpressed in precancerous and malignant lesions [33,34,35]. Its inhibition and the suppression of prostaglandin synthesis is widely accepted as the primary mechanism of the anticancer activity of NSAIDs.…”
Section: Resultsmentioning
confidence: 99%
“…However, some studies have concluded that a rather COX-independent mechanism may either contribute to or be exclusively responsible for the chemopreventive activity of NSAIDs [34,35,36]. …”
Section: Resultsmentioning
confidence: 99%
“…It was shown that PKG has both pro-and anti-proliferative effects on various tumor cell types. In some colon and breast cancer cells, PKG activation inhibits proliferation and increases apoptosis (Deguchi et al, 2004;Tinsley et al, 2011;Whitt et al, 2012), and these effects may be mediated by decreasing b-catenin levels (Tinsley et al, 2011;Whitt et al, 2012). In stark contrast, PKG facilitates pro-proliferative/anti-apoptotic signaling in neuronal, ovarian and lung tumor cells lines through inhibition of caspase activity and increasing expression of anti-apoptotic genes (Kim et al, 1999;Leung et al, 2010;Wong et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, another component reported to play an important role in the preconditioning pathways is PKG (22). Sulindac has been reported to be an inhibitor of PDE5, which raises cGMP levels and activates PKG (9). In the present study we tested the effect of inhibiting PKG using the known PKG inhibitor, Rp-Br-8-PET-cGMPS.…”
Section: Sulindac Protection Of Rpe Cells Involves Both Mitochondrialmentioning
confidence: 91%
“…Sulindac has also been shown to be an inhibitor of phosphodiesterase type 5 (PDE5) (9) and has been reported to react with both the peroxisome proliferator activator receptors (PPARs) and a truncated retinoic acid receptor (RXR) (10). The members of the PPAR nuclear receptor family are involved in certain key protective pathways in a variety of cell types and are known to complex with the RXR family (11).…”
mentioning
confidence: 99%